2006
DOI: 10.1086/507516
|View full text |Cite
|
Sign up to set email alerts
|

Precise Radial Velocities of Giant Stars. II. Pollux and Its Planetary Companion

Abstract: It has long been speculated that the observed periodic radial velocity pattern for the K giant Pollux might be explained in terms of an orbiting planetary companion. We have collected 80 high-resolution spectra for Pollux at Lick Observatory yielding precise radial velocities with a mean error of 3.8 m/s, providing the most comprehensive and precise data set available for this star. Our data confirm the periodicity previously seen in the radial velocities. We derive a period of 589.7±3.5 days and, assuming a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 20 publications
4
77
0
Order By: Relevance
“…We have continuously monitored the RVs of 373 G-and K-giant stars for more than a decade, resulting in several published planet detections (Frink et al 2002;Reffert et al 2006;Quirrenbach et al 2011;Mitchell et al 2013;Trifonov et al 2014). Typical masses in our sample are between ∼1-3 M and we reached RV precisions of ∼5-8 m s −1 .…”
Section: Observationsmentioning
confidence: 85%
“…We have continuously monitored the RVs of 373 G-and K-giant stars for more than a decade, resulting in several published planet detections (Frink et al 2002;Reffert et al 2006;Quirrenbach et al 2011;Mitchell et al 2013;Trifonov et al 2014). Typical masses in our sample are between ∼1-3 M and we reached RV precisions of ∼5-8 m s −1 .…”
Section: Observationsmentioning
confidence: 85%
“…They discovered long-period RV variations in three K giants and they proposed two viable hypotheses for these variations in radial velocity: substellar companions or rotational modulation. Recently Hatzes et al (2006) and Reffert et al (2006) confirmed that the initial RV variations found by Hatzes & Cochran (1993) in β Gem were in fact due to a planetary companion. Since the first unequivocal discovery of the first extrasolar planet around the K giant HD 137 759 (ι Dra) by Frink et al (2002), several giant stars have been found to host giant planets (Setiawan et al 2003a(Setiawan et al ,b, 2005Sato et al 2003;Hatzes et al 2005).…”
Section: Introductionmentioning
confidence: 84%
“…This makes giant stars suitable targets for extrasolar planet detection with the RV method. Frink et al (2002) discovered the first planetary companion around the K-giant star ι Dra (K2 III), and thereafter, several companions around K-giant stars have been reported using the precise RV method (Setiawan 2003;Setiawan et al 2003;Mitchell et al 1234;Hatzes et al 2005Hatzes et al , 2006Reffert et al 2006;Johnson et al 2007Johnson et al , 2008Döllinger et al 2007Döllinger et al , 2009de Medrios et al 2009;and Sato et al 2007and Sato et al , 2008aand Sato et al ,b, 2010. However, in K-giants the velocity variations caused by planetary companions can be blended with the stellar pulsations and surface activities, which complicates identification of planetary companions.…”
Section: Introductionmentioning
confidence: 99%